A proposal on Afghanistan integrated development programme implemented by BRAC: July 2002-June 2007 - BRAC (© BRAC, 2016)
1. Present situation of Afghanistan 2. BRAC 3. Micro finance programme 4. Employment and income generation 5. BRAC education programme 6. BRAC health programme 7. proposed activities in Afghanistan